Viktiga faktorer vid lantbrukares val av bank - Dahlsjö, Anders; Mattson, Lars-Johan; Svensson, Staffan (2010)
The bank market for farmers in Sweden is dominated by Swedbank and Landshypotek. One of the most aggressive challengers is Länsförsäkringar Bank, which in 2009 had seven per cent of the Swedish bank market for farmers, but 57 per cent of all new lending. This paper deals with the problem of new banks to break into the bank market where farmers are slow in terms of change in their attitudes and loyal to their banks. The study has been carried out in cooperation with Länsförsäkringar Gävleborg which is a new actor in the banking market and thus eager to take part in the outcome of the study. This essay thus seeks to examine the attitudes farmers have against bank switching and the factors that influence their choice of bank.